PENGARUH KONDISI FISIK DAN PSIKOLOGIS PADA MASA PUBERTAS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII DI MTsN PARAK LAWAS PADANG - Yulinar, Yulinar; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Problem in this research is how the effect of physic and physical condition the students grade eight MTsN Parak Lawas Padang concerning the result of study in puberty period. The purpose of this research are to describes: 1) desription of the physic and physical condition the student grade eight MTsN Parak Lawas Padang in puberty period, 2) description the result of study the student grade MTsN Parak Lawas Padang in puberty period, 3) effect of the psysic and physical condition concerning the result of study the student grade eight MTsN Parak Lawas Padang in puberty period. The research is quantitative descriptive. The population in this research is use simple random sampling technique. It is random pulling sample technique. Tool of the data collecting is questionnaire, and the data analysis technique is use percentage. The result of this research that: 1) description of the physic and physical condition the student grade eight MTsN Parak Lawas in puberty period is in good category, 2) description the result of study the students grade eight MTsN Parak Lawas Padang in puberty period is in law category, 3) effect of the physic and physical condition concerning the result of study the students grade eightÂ  MTsN Parak Lawas Padang in puberty period. We can conclude that, the are some effects in puberty period concerning study result of the students. Based on the research hoped to guide teacher can give comprehension to the students about puberty period, in order to the students can understanding the condition of their puberty period and donât be the problem in study to reach their development works.